Nurse education in Mbarara, Uganda - Kemp, Joan; Tindiweegi, Jocelyn (Journal of Advanced Nursing, 2001)
Aim: To describe the establishment of a professional development programme for qualified nurses at Mbarara University Teaching Hospital, Uganda. Background: Between 1997 and 1999, a group of hospital-based nurses and university lecturers in Hull, United Kingdom, planned and delivered a series of modules to set the Ugandan nurses on course for continuing professional development. Approach. A descriptive account of the delivery of the programme. Findings: Evaluation of the programme indicates that the nurses' morale was raised by satisfactory completion of the modules and that there were visible improvements in the organization of patient care in the hospital. Conclusions: This professional development programme was a learning experience for all the parties involved. Support from Hull for the education of nurses in Mbarara will continue.
Keywords: Education; Professional development; self-esteem; Developing world; Aid; Nursing; Uganda